The Effect of Focus Group Discussions on Enhancing Adolescent Knowledge of Reproductive Health - Salsabila, Karina Adra; Wardani, Dyah Wulan Sumekar Rengganis; Kusumaningtyas, Intan; Saftarina, Fitria (Medula, 2024)
Adolescents are individuals who have a great sense of curiosity, which can increase the risk of sexual and reproductive health issues. Adolescence is also experience puberty, in which the reproductive organs mature significantly. If these organs are not properly taken care, they can lead to various reproductive health issues. To prevent these issues, Various efforts are needed to increase adolescents' knowledges about reproductive health. One such effort can be giving health education using a method like Focus Group Discussion (FGD). This study aims to examine the impact of health education using the FGD method on improving knowledge about reproductive health among adolescents. The method that used in this study is a literature review. several literatures such as journals collected and analyzed them based on the findings from those studies. This research uses 8 journals, which consist  7 experimental research journals and 1 non-experimental research journal. The results, based on the analysis of these 8 previous studies, showed an improvement in the mean, median, as well as the minimum-maximum values before and after the intervention using the FGD method. The conclusion of this study is that there is a significant difference in the improvement of adolescents' knowledge about reproductive health before and after receiving health education through the FGD method.